About the electronic and photophysical properties of iridium(iii)-pyrazino[2, 3-f][1, 10]-phenanthroline based complexes for use in electroluminescent devices. Issue 2 (9th October 2015) - Cortés-Arriagada, Diego; Sanhueza, Luis; González, Iván; Dreyse, Paulina; Toro-Labbé, Alejandro
Abstract : Quantum chemistry calculations were used to investigate the electronic and luminescence properties of cyclometalated Iridium(iii ) complexes to be used as ionic transition metal complexes in light electrochemical cells. Abstract : A family of cyclometalated Ir III complexes was studied through quantum chemistry calculations to get insights into their applicability in light electrochemical cells (LECs). The complexes are described as [Ir(R-C^N)2 (ppl)] +, where ppl is the pyrazino[2, 3- f ][1, 10]-phenanthroline ancillary ligand. The modification of the HOMO energy in all the complexes was achieved by means of different R-C^N cyclometalating ligands, with R-ppy (phenylpyridine), R-pyz (1-phenylpyrazole) or R-pypy (2, 3′-bipyridine); in addition, inductive effects were taken into account by substitution with the R groups (R = H, F or CF3 ). Then, compounds with HOMO–LUMO energy gaps from 2.76 to 3.54 eV were obtained, in addition to emission energies in the range of 438 to 597 nm. The emission deactivation pathways confirm the presence of metal-to-ligand transitions in all the complexes, which allow the strong spin–orbit coupling effects, and then improving the luminescence performance. However, the coupling with ligand and metal centered excited states was observed for the blue-shifted emitters, which could result in a decrease of the luminescence efficiencies. Furthermore, ionization potentials, electron affinities and reorganization energies (for holes and electrons) were obtained to account for the injection and transport properties of all the complexes in electroluminescent devices.